Does Istishna and Qardh Financing Affect Profitability? (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study examines the effect of Istishna and Qardh financing on the Profitability of Islamic Commercial Banks for the 2015-2019 period. The data needed to support this research is secondary data, namely data obtained indirectly from the main source which is used as the object of research. The data is in the form of Islamic banking financial reports that are registered with the Financial Services Authority during the observation period from 2015 to 2019. The sampling method used in this study is to use non-probability sampling probability techniques, while the data processing method used by researchers is multiple regression analysis. The results of this study indicate that Istishna and Qardh financing does not simultaneously affect the profitability of Islamic Commercial Banks with a significance level of 0.074, greater than 0.05. Partially, Istishna Financing has no effect on profitability. This is explained from the results of the tcount of the Istishna financing variable of 0.045. Because tcount (0.045) is smaller than ttable (2.016) and the Sig value is 0.964> 0.05 and Qardh financing has an effect on profitability. This is explained from the results of the tcount (2.357)> t table (2.016), and the Sig value 0.023